Arginine Relieves the Inflammatory Response and Enhances the Casein Expression in Bovine Mammary Epithelial Cells Induced by Lipopolysaccharide. (23rd March 2016) - Wu, Tianyou; Wang, Chao; Ding, Luoyang; Shen, Yizhao; Cui, Huihui; Wang, Mengzhi; Wang, Hongrong
Abstract : As one of functional active amino acids, L-arginine holds a key position in immunity. However, the mechanism that arginine modulates cow mammary inflammatory response in ruminant is unclear. Therefore, this study was conducted to investigate the effects of L-arginine on inflammatory response and casein expression after challenging the bovine mammary epithelial cells (BMECs) with lipopolysaccharide (LPS). The cells were divided into four groups, stimulated with or without LPS (10  μ g/mL) and treated with or without arginine (100  μ g/mL) for 12 h. The concentration of proinflammatory cytokines, inducible nitric oxide synthase (iNOS), mammalian target of rapamycin (mTOR), and Toll-like receptor 4 (TLR4) signaling pathways as well as the casein was determined. The results showed that arginine reduced the LPS-induced production like IL-1 β, IL-6, TNF- α, and iNOS. Though the expression of NF- κ B was attenuated and the mTOR signaling pathway was upregulated, arginine had no effect on TLR4 expression. In addition, our results show that the content of β -casein and the total casein were enhanced after arginine was supplemented in LPS-induced BMECs. In conclusion, arginine could relieve the inflammatory reaction induced by LPS and enhance the concentration of β -casein and the total casein in bovine mammary epithelial cells.